Density profiles of small Dirac operator eigenvalues for two color QCD at nonzero chemical potential compared to matrix models - Akemann, Gernot; Bittner, Elmar; Lombardo, Maria Paola; Markum, Harald; Pullirsch, Rainer (Nuclear physics. Proceedings supplements, 2005)
We investigate the eigenvalue spectrum of the stagerred Dirac matrix in two color QCD at finite chemical potential. The profiles of complex eigenvalues close to the origin are compared to a complex generalization of the chiral Gaussian Symplectic Ensemble, confirming its predictions for weak and strong non-Hermiticity. They differ from the QCD symmetry class with three colors by a level repulsion from both the real and imaginary axis.
Gesehen am 13.10.2022